Pembangunan Kamus Bilingual Bahasa Sahu Tala'i - Indonesia Menggunakan Algoritma Aho-Corasick - Wikarsa, Liza; Suwanto, Thomas; Loha, Christ Henry (Jurnal Pekommas, 2024)
Nowadays, local languages gain less interest from the younger generation. This also happened to the Sahu Tala'i language which is a regional language originating from a tribe in the Sahu sub-district, West Halmahera district. Hence, users of this language are becoming fewer and will be threatened with extinction if not being consistently used. To preserve the language, this study built an Android-based bilingual, Sahu Tala'i, and Indonesian dictionary application, to provide access to the language for people in the Sahu sub-district and those who are interested in learning the language. This study uses the Aho-Corasick algorithm to accelerate word search by matching the strings used to determine the position of certain strings in a larger collection of strings. The test results showed that the implementation of the Aho-Corasick algorithm was successfully done to do a word search in the dictionary. Additionally, an audio feature to pronounce the word in the Sahu Tala'i accent/dialect and examples of the use of these words in sentences are provided in this bilingual dictionary.